Constraints on the performance and competitiveness of Tanzania's manufacturing exports - Roseline Nyakerario Misati; Kethi Ngoka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study sought to examine the main constraints to manufacturing export competitiveness in Tanzania. Using panel data for the period 1997-2018, the study established that supply-side factors dominate demand-side factors in explaining manufacturing export competitiveness. Specifically, the results revealed that foreign direct investment and tariffs have a negative and significant effect on export competitiveness in Tanzania, while infrastructure, total investment, labour productivity, and high institutional quality enhance manufactured exports. The study also showed scope for quality upgrading through technology diffusion as well as deeper integration of Tanzania's nascent global value chains by building on existing competencies and negotiating deep trade agreements to increase market reach. Accordingly, measures to increase investment in infrastructure, strengthen institutional frameworks, and further develop human capital can boost export competitiveness in Tanzania. In addition, export competitiveness can be enhanced through reduction of tariffs and incentives to use cheaper value-adding intermediate inputs.
Keywords: C26; F14; L60; 330; competitiveness; manufactured exports; global value chains; Tanzania